Einfluss von Instationarität auf die Wartezeit an Knotenpunkten mit und ohne Lichtsignalanlage - Leyn, Ulrike (Schriftenreihe des Instituts für Verkehrswesen, Karlsruher Institut für Technologie, 2017)
Vehicle delay is used to assess the level of service for intersections. The impact of non-stationary arrival flow rates has only partly been included in calculation methods. Empirical data is used to show that traffic volume during the peak hour can be distributed in very different forms. A microscopic traffic simulation study is carried out in order to assess their impact on the delay. As a result a new factor is proposed to include non-stationarity more precisely in the calculation of delay.